Inflammatory Markers in Rheumatoid Patients and Cardiac Function: Insights from an Iranian University Hospital - Fatemeh Omidi; Parisa Delkash (Novelty in Biomedicine)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disorder associated with increased cardiovascular morbidity and mortality. This study investigated the association between RA inflammatory markers, such as erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and various cardiac function parameters.